2010
DOI: 10.17796/jcpd.35.2.u6142007hj421041
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage and Shear Punch Bond Strength in Class II Primary Molars Cavities Restored with Low Shrink Silorane Based versus Methacrylate Based Composite using Three Different Techniques

Abstract: Objectives: This in vitro study aimed to evaluate the gingival microleakage in class II cavities in primary molars restored with a low shrink silorane resin composite (Filtek P90) or a nanohybride composite resin(Filtek supreme XT) using three different techniques, (total bonding, closed or open sandwich techniques)lined by nano-filled resin modified glass ionomer cement RMGIC (Ketac N100). Additionally, the shear punch bond strength between the two types of composite and KN100 was also examined. Study design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…So far, only Fahmy and Farrag 27 have recently evaluated microleakage in Class II primary molar cavities restored with NI/silorane or methacrylate nanofilled composite (open and closed sandwich) and total bonding. They found superior marginal sealing with total bonding compared with two sandwich techniques.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only Fahmy and Farrag 27 have recently evaluated microleakage in Class II primary molar cavities restored with NI/silorane or methacrylate nanofilled composite (open and closed sandwich) and total bonding. They found superior marginal sealing with total bonding compared with two sandwich techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested in some studies that cohesive fracture in the substrate can indicate a high bond strength (11); however, some others have reported no relationship between bond strength and fracture type (28,29). In the previous studies, most fractures of GICs and RMGICs have been considered to be of the cohesive type (30,31), which can be attributed to the physical and mechanical drawbacks of the tests used.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have indicated that cohesive fracture in the substrate is a reflection of a high bond strength;[22] however, some others have reported no relationship between the bond strength and fracture type. [23] In the majority of previous studies most of the fractures of GICs and RMGICs have been of the cohesive type,[24] which might be attributed to the physical and mechanical shortcomings of the tests used in those studies. For example, stresses which are out of the center during the test, small porosities within the cement, which act as foci with the potential of generating stresses and differences in the setting reaction of GI and composite resin[61120] might be factors responsible for cohesive fractures.…”
Section: Discussionmentioning
confidence: 99%